Quality Improvement to Reduce Paper Bags Defects Using DMAIC Method in Cement Industry - Fathurohman, Dimas Mukhlis; Dewi, Intan Novita; Firman, Firman (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Improving quality can affect increasing customer satisfaction, business profitability and business competitiveness to maintain industry sustainability in the future. This research focuses on the manufacturing process of paper bags in the cement industry, especially on high product defects. This research uses the Six Sigma method. DMAIC (Define, Measure, Analyze, Improve, and Control) methodology is supported by quality tools that have successfully analyzed and made recommendations for corrective actions. The method was used to propose several recommendations. After improvements were made using the Six Sigma method such as providing training to tubbing machine operators every three months and briefing the operators before work, there was an increase in the sigma value from 4.65 to 5.04 and there was a 14% decrease in the company’s operational costs and rework costs. Based on the hypothesis test, there is a difference in the average number of defects between before and after the improvement. Improving quality can affect increasing customer satisfaction, increasing business profitability and increasing business competitiveness to maintain industry sustainability in the future.